Some technical modifications in oesophageal resection for carcinoma - Stephen, S. J. (1972)
The frequency of oesophageal carcinoma in Ceylon provides an opportunity for elaborating certain modifications in the technique of oesophageal resection. Initial subadventitial ligation of oesophageal branches of the aorta renders the operative field relatively bloodless, thus facilitating the removal en bloc of the tumour together with the lymphatic and loose cellular tissue, as well as the adventitia of the aorta when it is involved. The division of the oesophagus above the growth in an oblique plane, leaving a posterior flap, helps to minimize the incidence of fibrous strictures and anastomotic leaks. In fashioning the stomach tube, the stomach is divided just proximal to the beginning of the left gastro-epiploic arch. This procedure ensures that the blood supply to the gastric component of the oesophagogastric anastomosis is least disturbed. In cases where the transverse colon and hepatic flexure are used as an interposition, a dual blood supply derived from the middle colic as well as the ascending branch of the left colic artery is retained. This procedure increases the margin of safety in case one artery obstructs.